2021
DOI: 10.1021/acs.jpcc.1c06841
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Magnetic Hardness of Fe3Se4 via Cu Doping

Abstract: The influence of Cu doping on the structural and magnetic properties of the Fe3Se4 ferrimagnet has been investigated by a combination of X-ray diffraction, Raman spectroscopy, X-ray absorption spectroscopy, and magnetic measurements. While the effects of dopants with ionic radii closer to those of the Fe sites in Fe3Se4 had been studied before, Cu is a less conventional dopant, due to its smaller size (at the same ionic charge) and preference for lower coordination numbers. A (Fe1–x Cu x )3Se4 series, where x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is also likely that these signals were overlapped with a B 1g peak at 196 cm −1 of Fe vibrations, which also include a E g peak at 248 cm −1 . [ 52 ] The slightly different position of the A 1g Se peak for Co 1 Fe 1 Se n as compared to that recorded for CoSe n might be possibly associated with the change in the selenium–metal bond lengths.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also likely that these signals were overlapped with a B 1g peak at 196 cm −1 of Fe vibrations, which also include a E g peak at 248 cm −1 . [ 52 ] The slightly different position of the A 1g Se peak for Co 1 Fe 1 Se n as compared to that recorded for CoSe n might be possibly associated with the change in the selenium–metal bond lengths.…”
Section: Resultsmentioning
confidence: 96%
“…It is also likely that these signals were overlapped with a B 1g peak at 196 cm À1 of Fe vibrations, which also include a E g peak at 248 cm À1 . [52] The slightly different position of the A 1g…”
Section: Structure and Morphologymentioning
confidence: 99%
“…With x = 0.03 replacement, the T C stayed almost same, but the magnetization rose noticeably, and thus, the (BH) max increased by 130%. Moreover, a recent study reported a significantly enhanced H C from 17.7 kOe to 26.2 kOe at x = 0.10 for (Fe 1−x Cu x ) 3 Se 4 samples prepared by the solvothermal method [28]. Previous calculations, on the other hand, were mostly limited to experimental investigations.…”
Section: Introductionmentioning
confidence: 99%